2015
DOI: 10.4172/2165-7920.1000548
|View full text |Cite
|
Sign up to set email alerts
|

Primary Synovial Sarcoma of the Mediastinum: A Case Report and Review of the Literature

Abstract: Background: Synovial sarcomas most commonly occur in the soft tissues of the extremities of young adults. A primary occurrence in the mediastinum is very rare with only a few reported cases in the world literature. Study aims: to insist on the rarity of this pathology, its imaging features and the importance for recognizing unusual presentation of this aggressive neoplasm to aid appropriate clinical management. Cases: Here in, we report a rare case of primary monophasic spindle cell synovial sarcoma of the med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Peripheral calcifications were described in some cases. In advanced stages, invasion and infiltration of surrounding tissue, and ipsilateral pleural effusion may be presented (6) .…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral calcifications were described in some cases. In advanced stages, invasion and infiltration of surrounding tissue, and ipsilateral pleural effusion may be presented (6) .…”
Section: Discussionmentioning
confidence: 99%
“…For his part, Archie Carroll enriched the definition of CSR in 1979 by introducing a broader framework. He suggested that CSR encompasses not only the economic and legal responsibilities of business, but also ethical and discretionary aspects, creating a more holistic approach to CSR [18]. ISO 26000, published in 2010, offers a guide to CSR, defining it as an organization's responsibility for the impacts of its decisions and activities on society and the environment.…”
Section: The Main Definitions Of Csr and Their Evolution Over Timementioning
confidence: 99%
“…It primarily occurs in soft tissues of the extremities, often near joint capsules and tendon sheaths, but also can occur in other areas of the body, including the mediastinum [ 1 ]. Although it is known as "synovial", it does not originate from synovial tissue but rather from pluripotent mesenchymal tissue which commonly found in tendons and joint fibers [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemistry is ideal for distinguishing these subtypes. SS is positive for epithelial membrane antigen (EMA), bcl-2, CD99, S-100, and vimentin and negative for myoD1 and myogenin [ 2 ]. More than 95% of SS cases have the t(X; 18)(p11; q11) translocation, resulting in SS18-SSX fusion genes [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation